Anlotinib combined with TAS-102 as the third-line treatment for a patient with metastatic colon cancer: A case report - Li, Qizheng; Zhang, Xia; Fan, Buqun; Yang, Yudie; Cui, Xiaonan; Zhang, Jie; Jiang, Kaiteng; Zhang, Chunxia; Zhang, Bin (Frontiers in Oncology, 2022)
Chemotherapy combined with targeted therapy is a first-line and second-line treatment for metastatic colorectal cancer, which has brought survival benefits to mCRC patients in the era of non-immunotherapy, however, disease progression is inevitable. After the failure of second-line chemotherapy, treatment compliance and the physical tolerance of patients both decrease. Choosing an appropriate third-line treatment regimen is key to prolonging survival and improving quality of life. The few side effects of TAS-102(a novel cytotoxic antitumor drug) has become the main reason for patients to choose the drug, clinical trial data for progression free survival are lacking. The exploration of third-line treatment regimens with drug combinations has attracted much attention. This article reports a case of metastatic colon cancer, the patient was eventually treated with anlotinib combined with TAS-102 as the third-line treatment. The treatment has shown good efficacy, with a long PFS benefit and mild adverse reactions. We believe that anlotinib combined with TAS-102 is a promising third-line treatment regimen for refractory mCRC, and we hope to provide a reference for the clinical exploration of optimal third-line combination treatment regimens.